THE ROLE OF OWNERSHIP CONCENTRATION AS MODERATION ON BIOLOGICAL ASSET INTENSITY, COMPANY SIZE, AND FIRM GROWTH ON BIOLOGICAL ASSET DISCLOSURE IN AGRICULTURAL INDUSTRY IN INDONESIA - Rezensky, Rosalia; Lukman, Hendro (International Journal of Application on Economics and Business, 2023)
Disclosure in financial statements is now important for users. The purpose of this study is to empirically prove whether there is an influence between Biological Asset Intensity, Company Size, and Firm Growth on Biological Asset Disclosure. In addition, this study wants to see whether the Ownership Concentration moderates the relationship between those variables. The population of this study is agricultural companies listed on the Indonesia Stock Exchange (IDX) in the period 2018 to 2020. Purposive sampling was usedthe sampling technique and the total sample obtained was 51 samples. The data were processed using SPSS ver 26.0 with multiple regression analysis and Moderated Regression Analysis (MRA) methods. The results of the analysis of this study found that Biological Asset Intensity, Company Size, and Firm Growth did not have a significant effect on Biological Asset Disclosure. The results of the moderation analysis, Ownership Concentration proves to strengthen the relationship between Biological Asset Intensity and Company Size on Biological Asset Disclosure. However, Ownership Concentration has proven to weaken the relationship between Firm Growth and Biological Asset Disclosure.The implication of this research is the need to increase the role of centralized ownership in terms of financial statements in order to provide added value for investors.